PENGARUH FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMP NEGERI 14 KOTA BANDA ACEH - Ari Fiki; Anwar Anwar; Khairul Aswadi; Cut Nya Dhin; Abubakar Abubakar; Muhammad Junaidi; Arfriani Maifizar (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to determine the effect of learning facilities on learning outcomes at SMP Negeri 14 Banda Aceh City. This research is quantitative descriptive, namely research on data collected and expressed in the form of numbers, although it is also qualitative data. The population in this research is class students. The population in this research is all class IIX students in the odd semester of SMP Negeri 14 Banda Aceh in the 2017/2018 academic year. The sample was chosen by random sampling from one of class IIX which consists of 2 classes, namely IIX-1, IIX-2. The sample selected for this research was class IIX-2 with a total of 48 students. The total number of class IIX students is 48. Data collection techniques use interviews, questionnaires and documentation. The analytical method used is simple regression analysis. Research results: Learning achievement at SMP Negeri 14 Banda Aceh City is quite good as seen from the report card scores. Study facilities for students at SMP Negeri 14 Banda Aceh City are computers, teaching material books, study tables, stationery, whiteboards, markers and study chairs. The results of the calculations obtained ttable test 2.063 and tcount 2.255, so tcount>ttable, so accept Ha reject H0 so it can be concluded that there is an influence between home learning facilities on learning achievement at SMP Negeri 14 Banda Aceh city.